Aldosterone, not estradiol, is the physiological agonist for rapid increases in cAMP in vascular smooth muscle cells - Christ, Michael; Günther, Andreas; Heck, Marina; Schmidt, Bernhard; Falkenstein, Elisabeth; Wehling, Martin (Circulation, 1999)
Background—Steroid-induced gene regulation in the endocrine tissues and vascular wall is achieved through the interaction of specific receptor proteins and promoters of target genes. In addition to these delayed steroid actions, rapid effects of steroids have been reported in various tissues that were clearly incompatible with the classic theory of genomic steroid action. - - Methods and Results—Because high doses of 17β-estradiol have been shown to modulate intracellular cAMP levels in vascular smooth muscle cells, steroid-induced stimulation of adenylate cyclase stimulation and phosphorylation of cAMP response element binding protein was investigated in porcine coronary artery vascular smooth muscle cells. Aldosterone induces a ≈1.5- to 2.5-fold increase in intracellular cAMP levels (EC50 ≈0.01 to 0.1 nmol/L) within 1 minute, whereas 17β-estradiol and hydrocortisone act only at supraphysiological concentrations (10 μmol/L). Aldosterone-induced changes in intracellular cAMP are calcium dependent; they are not blocked by inhibitors of mineralocorticoid receptors, transcription, or protein synthesis. In addition, aldosterone induces a time-dependent phosphorylation of cAMP response element binding protein with potential transcriptional importance. - - Conclusions—A nongenomic modulation of vascular smooth muscle cells by aldosterone is consistent with the data that aldosterone, not estrogen, is the physiological stimulus for cAMP.